A Combined Experimental–Theoretical Study on Diels‐Alder Reaction with Bio‐Based Furfural: Towards Renewable Aromatics. Issue 1 (16th October 2020) - van Scodeller, I; De Oliveira Vigier, Karine; Muller, Eric; Ma, Changru; Guégan, Frédéric; Wischert, Raphael; Jérôme, François
Abstract: The synthesis of relevant renewable aromatics from bio‐based furfural derivatives and cheap alkenes is carried out by using a Diels‐Alder/aromatization sequence. The prediction and the control of the ortho / meta selectivity in the Diels‐Alder step is an important issue to pave the way to a wide range of renewable aromatics, but it remains a challenging task. A combined experimental‐theoretical approach reveals that, as a general trend, ortho and meta cycloadducts are the kinetic and thermodynamic products, respectively. The nature of substituents, both on the dienes and dienophiles, significantly impacts the feasibility of the reaction, through a modulation on the nucleo‐ and electrophilicity of the reagents, as well as the ortho / meta ratio. We show that the ortho / meta selectivity at the reaction equilibrium stems from a subtle interplay between charge interactions, favoring the ortho products, and steric interactions, favoring the meta isomers. This work also points towards a path to optimize the aromatization step. Abstract : A perfect combination : Renewable aromatics are synthesized from bio‐based furfural and various alkenes by using a Diels‐Alder/aromatization sequence. This investigation aims at rationalizing, and even predicting, not only the feasibility of the Diels‐Alder reaction but also the effect of substituents on the ortho / meta selectivity.